Comparative analysis of global practices in the management of colchicine-resistant familial Mediterranean fever: a CliPS network analysis - Haslak, Fatih; Oner, Nimet; Elhani, Inès; Hinze, Tanja; Mamutova, Anna; Bourguiba, Rim; Kasap Cuceoglu, Muserref; Pateras, Konstantinos; Aviel, Yonatan Butbul; Delplanque, Marion; Caorsi, Roberta; Šestan, Mario; et al. (BMJ Publishing Group Ltd, 2025)
Although colchicine is the mainstay of familial Mediterranean fever (FMF) treatment, 5-10% of patients are considered to have colchicine resistance (CR). However, there is no globally agreed CR definition or indications for biological disease-modifying anti-rheumatic drugs (bDMARDs).
Keywords: amyloidosis; Familial Mediterranean Fever; Biological Therapy; Interleukin 1 Receptor Antagonist Protein